Genetic Diversity and Pathogenicity of the Fusarium Species Complex on Soybean in Serbia - Petrović, Kristina (Plant disease, 2024)
Using morphological and cultural characteristics for identification, 36 Fusarium isolates were recovered from diseased roots, stems, and seeds of soybean from several localities throughout Vojvodina Province, Serbia. Based on molecular characterization, 12 Fusarium species were identified: F. acuminatum, F. avenaceum, F. commune, F. equiseti, F. graminearum, F. incarnatum, F. oxysporum, F. proliferatum, F. solani, F. sporotrichioides, F. subglutinans, and F. tricinctum. The elongation factor 1-α-based phylogeny grouped the isolates into 12 well-supported clades, but polymorphisms among sequences in some clades suggested the use of the species complex concept: (i) F. incarnatum-equiseti species complex (FIESC)-F. incarnatum and F. equiseti; (ii) F. oxysporum species complex (FOSC)-F. oxysporum; (iii) F. solani species complex (FSSC)-F. solani; and (iv) F. acuminatum/F. avenaceum/F. tricinctum species complex (FAATSC)-F. acuminatum, F. avenaceum, and F. tricinctum. Pathogenicity tests showed that the most aggressive species causing soybean seed rot were F. sporotrichioides, F. graminearum, FIESC, and F. avenaceum. Furthermore, F. subglutinans, FSSC, and F. proliferatum showed a high percentage of pathogenicity on soybean seeds (80 to 100%), whereas variability in pathogenicity occurred within isolates of F. tricinctum. FOSC, F. commune, and F. acuminatum had the lowest pathogenicity. To our knowledge, this is the first study of the characterization of Fusarium species on soybean in Serbia. This study provides valuable information about the composition of Fusarium species and pathogenicity that will be used in further research on soybean resistance to Fusarium-based diseases